Стихотворения: пер. с груз. / Реваз Амашукели - Амашукели Реваз (Советский писатель, 1990)
Экземпляры: КХ (20120403) / Инвентарный номер: 972009 / Цена: 0.50 / Сис.шифр: С(Груз) / Авт.знак: А 61 / ГРНТИ: 17 / ББК: 84(2)